Propagation of acid lime (Citrus aurantifolia) through nucellar seedlings: farmers perception (Current Horticulture, 2024)
Citrus (Citrus spp.) fruits, which include mandarin, sweet oranges, lemon, lime, pummelo etc., are primarily consumed as fresh fruits and also processed, mainly to prepare squash, juice, marmalade and pickles (Tripathi et al. 2018). Acid lime (Citrus aurantifolia Swingle) is commercially cultivated in Maharashtra, Andhra Pradesh, Karnataka, Tamil Nadu, Gujarat and Bihar. Acid lime or kagzi lime is a small tree of staggering habit with small, round or oval, greenish yellow fruits and is commercially propagated by seeds in India, as it comes true-to-type because of high degree (39-60%) of nucellar embryony and least chance of contamination of viral diseases, besides seed propagation being the economical and easiest method (Mukundalakshmi et al., 2016).